Where Technology Goes to Die: Representations of Electronic Waste in Global Television News. Issue 2 (4th March 2017) - Andersson, Linus
ABSTRACT: This article analyzes how electronic waste (e-waste) gets represented in television news stories. The main objective is to present a perspective on how a "low-frequency" emergency (i.e. a lengthy and ongoing state of environmental emergency) is presented as a newsworthy issue. Drawing on literature on televised "distant suffering, " the article engages in a multimodal text analysis of four news stories about e-waste. The findings show how on-location reports from e-waste dumping sites make use of sublime imagery in the visual representations; how e-waste dumping sites are presented as strange spaces, with no clear and comprehensible history; and finally, that the representations suggest an ambivalence and uncertainty when it comes to agency (who is responsible and what can be done?). The article ends with a discussion of the implications of this mode of representation and its effectiveness in eliciting an appropriate response to the harms caused by e-waste.